Proposed marketing strategy for an overseas education consultant in Indonesia - Kartika, Allegra Putri; Wibowo, Satya Aditya (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2022)
A well-built marketing strategy enables Yes Study Indonesia to establish and sustain its competitive advantage, as well as to compete in fierce competition among other overseas educational consultants in Indonesia. This article aims to analyze the external environment and the internal environment of the business. SWOT analysis was then used to summarize the internal and external analysis and define the company’s strengths, weaknesses, opportunities, and threats. The quantitative research method was conducted with the 163 questionnaire respondents to be analyzed to understand the point of view of potential customers toward studying abroad and the use of overseas educational agencies. Meanwhile, in-depth interviews with the management, staff, past students, and parents were conducted as a qualitative research methodology. There are several external and internal factors that can impact how Yes Study Indonesia can plan a suitable marketing strategy. Starting with the external factors, government support in exposing more opportunities for Indonesian students to study abroad and the trend of distance learning due to the pandemic have presented themselves as opportunities for Yes Study Indonesia. Meanwhile, the easiness of legal requirements and economic downturn possess as challenges for the company.